The effectiveness of the use of metacognition-based industrial electronic learning tools in growing higher order thinking skills (HOTS) - Purnamawati Purnamawati; Saliruddin Saliruddin (Jurnal Pendidikan Vokasi, 2017)
The aims of this research were to: (1) find out the response of students to metacognition-based industrial electronic learning in growing the ability of Higher Order Thinking Skills (HOTS) in vocational secondary schools, (2) describe the learning outcomes of the students in the field of industrial electronics based on metacognition with direct learning method, and (3) generate the effectiveness of metacognition-based industrial electronics learning in growing HOTS capabilities in vocational secondary schools. The research was Quasi-experimental type, while the research design used Pretest-Posttest Control Design with the research subject was the students of Public Vocational Secondary Schools in Makassar City in the field of Industrial Electronics Expertise. Data collection techniques were conducted by questionnaire and learning outcomes test. The result showed that: (1) the students' response of experimental class was higher that control class, (2) the learning outcomes of experimental class was higher than control class, and (3) the use of metacognition-based tools for industrial electronics learning was effective. This learning method could grow the HOTS capabilities of the students in solving the problems of industrial electronics circuit.